An unusual case of mediastinal lymphadenopathy and fever. Issue 3 (3rd July 2019) - Solverson, Kevin J.; Chan, Wilson; Tremblay, Alain
Abstract: We present a case of a 65 year old male who developed recurrent fevers and weight loss over a 4-week period after travel to Mexico. He was found to have extensive mediastinal lymphadenopathy on CT chest with normal lung parenchyma. Bronchoscopy with endobronchial ultrasound-guided transbronchial needle aspiration of multiple mediastinal nodes was performed. During the bronchoscopy an endobronchial lesion situation at the entrance of the right mainstream bronchus was noted and biopsied. The initial gram stain and acid fast bacilli were negative for organisms from the mediastinal lymph nodes and histology showed non-necrotizing granulomas without evidence of malignancy. At 24 hours of incubation nondescript colonies of Gram-negative bacilli were present and later confirmed through PCR to be Burkholderia pseudomallei . The patient was treated with intravenous ceftazidime for 2 weeks and then 12 weeks of trimethoprim-sulfamethoxazole. Follow-up CT imaging at 8 weeks showed resolution of the mediastinal lymphadenopathy and the patients clinical symptoms had resolved. Burkholderia pseudomallei is endemic to South East Asia and Oceania; however, cases have been reported in the Mexico and Central America. This case highlights the importance of considering a broad differential diagnosis for mediastinal lymphadenopathy in the returning traveler.